Oral prosthetic microbiology: aspects related to the oral microbiome, surface properties, and strategies for controlling biofilms - Monteiro, Douglas Roberto [UNESP]; de Souza Batista, Victor Eduardo; Caldeirão, Anne Caroline Morais; Jacinto, Rogério de Castilho [UNESP]; Pessan, Juliano Pelim [UNESP] (Taylor & Francis, 2021)
The oral cavity is an environment that allows for the development of complex ecosystems; the placement of prosthetic devices as a consequence of partial or total tooth loss may alter the diversity of microbial communities. Biofilms on the surface of materials used in dental prostheses can promote important changes in the mechanic and aesthetic properties of the material itself and may cause local and systemic diseases for the prosthetic wearer. This review presents the main features of the oral microbiome associated with complete or partial dentures and dental implants. The main diseases associated with microbial colonization of prosthetic surfaces, factors that may affect biofilm formation on prosthetic materials, as well as novel alternative therapies aiming to reduce biofilm formation and/or to eradicate biofilms formed on these materials are also explored.
Keywords: Antimicrobials; biofilms; biomaterial; diseases; fungi; microbial contamination